The Effect of Corporate External Restructuring on the Performance of Financial Institutions in Nigeria: A Review - Amire, Comfort .M.; Amire, Peter .O. Ebunoluwafunmi (International Journal of Economics and Financial Modelling, 2016)
The need for financial institutions anywhere in the world cannot be over-emphasized. The daily business transactions carried out by individuals, firms and corporate entities underscores the need for a better and performing financial institutions in Nigeria .This paper specifically focused on Banks as the leading financial institution in Nigeria, the problems and challenges associated with the financial systems in Nigeria before the intervention of the Apex regulatory body (Central Bank of Nigeria) through the recapitalization directive, the effect of the recapitalization and restructuring process on the industry and the role of the Central Bank of Nigeria in sustaining, maintaining and enforcing the recapitalization directive.